Methanogenic Pathway and Archaeal Communities in Three Different Anoxic Soils Amended with Rice Straw and Maize Straw - Conrad, Ralf; Klose, Melanie; Lu, Yahai; Chidthaisong, Amnat (Frontiers in Microbiology, 2012)
Addition of straw is common practice in rice agriculture, but its effect on the path of microbial CH4 production and the microbial community involved is not well known. Since straw from rice (C3 plant) and maize plants (C4 plant) exhibit different δ13C values, we compared the effect of these straw types using anoxic rice field soils from Italy and China, and also a soil from Thailand that had previously not been flooded. The temporal patterns of production of CH4 and its major substrates H2 and acetate, were slightly different between rice straw and maize straw. Addition of methyl fluoride, an inhibitor of aceticlastic methanogenesis, resulted in partial inhibition of acetate consumption and CH4 production. The δ13C of the accumulated CH4 and acetate reflected the different δ13C values of rice straw versus maize straw. However, the relative contribution of hydrogenotrophic methanogenesis to total CH4 production exhibited a similar temporal change when scaled to CH4 production irrespectively of whether rice straw or maize straw was applied. The composition of the methanogenic archaeal communities was characterized by terminal restriction fragment length polymorphism (T-RFLP) analysis and was quantified by quantitative PCR (qPCR) targeting archaeal 16S rRNA genes or methanogenic mcrA genes.. The size of the methanogenic communities generally increased during incubation with straw, but the straw type had little effect. Instead, differences were found between the soils, with Methanosarcinaceae and Methanobacteriales dominating straw decomposition in Italian soil, Methanosarcinaceae, Methanocellales, and Methanobacteriale in China soil, and Methanosarcinaceae and Methanocellales in Thailand soil. The experiments showed that methanogenic degradation in different soils involved different methanogenic population dynamics. However, the path of CH4 production was hardly different between degradation of rice straw versus maize straw and was also similar for the different soil